Thermal treatment of superconductor thin film of the BSCCO system using domestic microwave oven - Silveira, J. B. [UNESP]; Carvalho, C. L. [UNESP]; Torsoni, G. B. [UNESP]; Aquino, Hermes Adolfo de [UNESP]; Zadorosny, R. [UNESP] (Elsevier B.V., 2012)
In this work, we report the preparation of a superconductor thin film of the BSCCO system using a good quality powder with nominal composition Bi1.8Pb0.4Sr2CaCu2Ox which was thermally treated using a domestic microwave oven (2.45 GHz, 800 W). This film was grew on a single crystal of LaAlO3 (1 0 0) substrate and exhibited a crystalline structure with the c-axis perpendicular to the plane of the substrate. An onset superconducting transition temperature was measured at 80 K. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: BSCCO; Microwave; Film; Thermal treatment